Principals' Perceptions of Community and Staff Involvement in Shared Decision Making - David W. Brown; Rebecca E. Carr; Constance M. Perry; Walter G. McIntire (Journal of Research in Rural Education, 1996)
Our study assessed Maine principals' perceptions ofthe present status ofshared decision making in their schools and their view of the ideal level of participation ofstaff and community members. In addition, principals' ideal level of involvement was examined by gender and grade level. The results show that principals desire greater involvement ofboth these groups than actually exists.